Study of Laser Assisted Hatching for Fertility Outcome in Intra Cytoplasmic Sperm Injection and IVF Cycles - Habibzadeh, Victoria; Mirshekari, Tooraj Reza; Ganjizadegan, Aboozar (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: Implantation of transferred embryos in the uterus after IVF_ICSI cyclesis an important process that less information about it is available. Zona hatching method is a suggested approach for this goal. The aim of this research is about performance of zona hatching by laser. METHODS: In this study 32 patients that enrolled had IVF/ICSI cycles depend on inclusion criteria of study that they included patients who were more than 35 years old, at least one previous failure of IVF, thickness or hardness of zona pelucida, the laser hatching performed on them. Then the pregnancy test (ß-subunit) was done and patients with a positive result are followed with vaginal ultra sonography. RESULTS: Our successful results belonged to the patients who had more than 35 years old. So 50% of pregnancy was positive and then 20% about the zona pelucida thickness and minimum results were about the previous failure of IVF/ICSI cycles. CONCLUSION: Laser hatching on the embryos of women more than 35 years old with IVF/ICSI cycle will optimize pregnancy outcomes